Review article: A variable level of prostate specific antigen and its relative tests and their probable explanatory diagnosis - Kudhair, Ahmed Hassan; Abbas, Hanan Diekan (Technium BioChemMed, 2022)
prostate specific antigen is a glycoprotein that liquefy the semen normally. It suppose to be in a very low level abnormally and increase in cases of infection of the prostrate, hyperplasia and tumor. Due to increase and decrease in many other cases not only a tumor and due to high percent of existence in many normal fluids and many other tumor, it somewhat reduce its specifity and sensitivity and so it supported by other test. Aim: it to predict whether that tumor marker is sufficient to the diagnosis of the prostate tumor. Nowadays it had been seen that this tumor marker is secreted from many other fluid beside the prostate gland and found in many other tumor beside the prostate tumor and so it is better to be supported by many other assessments and clinical and histological steps for making a definite decision.